2012
DOI: 10.1128/aac.05344-11
|View full text |Cite
|
Sign up to set email alerts
|

Product Quality of Parenteral Vancomycin Products in the United States

Abstract: In response to concerns raised about the quality of parenteral vancomycin products, the U.S. Food and Drug Administration (FDA) is investigating the product quality of all FDA-approved parenteral vancomycin products available in the United States. Product quality was evaluated independently at two FDA Office of Testing and Research (FDA-OTR) sites. In the next phase of the investigation, being done in collaboration with the National Institute of Allergy and Infectious Diseases, the in vivo activity of these pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
26
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(28 citation statements)
references
References 8 publications
(12 reference statements)
2
26
0
Order By: Relevance
“…Analytical chemistry data for six vancomycin generics obtained by FDA scientists demonstrated that factor B and total impurities made up 90 to 95% and 5 to 10%, respectively, which was in full compliance with the U.S. Pharmacopeia (11)(12)(13). Similarly, no significant differences were detected among six French vancomycin generics based on the rabbit endocarditis model used by scientists from the Pontchaillou University Hospital at Rennes (14).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Analytical chemistry data for six vancomycin generics obtained by FDA scientists demonstrated that factor B and total impurities made up 90 to 95% and 5 to 10%, respectively, which was in full compliance with the U.S. Pharmacopeia (11)(12)(13). Similarly, no significant differences were detected among six French vancomycin generics based on the rabbit endocarditis model used by scientists from the Pontchaillou University Hospital at Rennes (14).…”
mentioning
confidence: 99%
“…These studies were done several years after the innovator had abandoned antimicrobial business, selling its vancomycin production secrets to all interested parties, while our research took place before and after that decision (7,8). The discontinuation of the innovator made vancomycin a less-than-ideal choice to study the mechanisms behind therapeutic nonequivalence, but the FDA reports showed that U.S. generics differed slightly in the amounts and variety of impurities and degradation products (11,12). Although such differences do not violate the pharmacopeia, the fact is that vancomycin generics are not chemically identical.…”
mentioning
confidence: 99%
“…Furthermore, the manufacturer of the generic drug needs to show that its product meets established purity, potency, quality, and identity standards. For the parenteral vancomycin products, the purity and related substance impurities are assessed by quantifying the percentage of the active component of vancomycin (vancomycin factor B) and the individual impurities in the product by a high-pressure liquid chromatography (HPLC) method (3). The potency is measured using the bioassay described by the United States Pharmacopeia (USPϽ81Ͼ) (4,5).…”
mentioning
confidence: 99%
“…A second limitation of our study is that we evalu- Vancomycin is manufactured via a fermentation process, which produces many structurally similar components and degradation products, along with the active vancomycin B component. Some of these impurities exhibit antimicrobial activity, such as monodechlorovancomycin, which has about half the activity of vancomycin B, whereas others have no antimicrobial activity (30). As such, the U.S. Food and Drug Administration (FDA) evaluates both the purity and potency of vancomycin preparations.…”
Section: Discussionmentioning
confidence: 99%
“…The United States Pharmacopeia (USP) acceptance criteria for vancomycin hydrochloride products are a purity of Ն80.0% for vancomycin B, with Յ9.0% of each individual impurity, and a potency of 90 to 115% (31). Two recent studies conducted by the FDA in response to concerns regarding the potency and purity of generic vancomycin for injection (30) found 89 to 95% purity when measured by both the British Pharmacopoeia and USP methods, as well as a potency that ranged from 97 to 112% (32), compared to the USP standard, for six generic vancomycin products available in the United States. These differences, while within USP standards, may be a source for vancomycin MIC variability such as that observed in our study.…”
Section: Discussionmentioning
confidence: 99%